2020
DOI: 10.1177/1369433220968451
|View full text |Cite
|
Sign up to set email alerts
|

A review on seismic behavior of ultra-high performance concrete members

Abstract: Ultra-high performance concrete (UHPC) is a type of cementitious composite, and demonstrates very high compressive strength and good ductility. The favorable ductility and energy dissipation capacity of UHPC material make it possible to achieve excellent seismic performance in all kinds of structural members. The paper reviewed the recent progress on the seismic behavior of UHPC members, including flexural members (beams and plates), compressive members (columns and shear walls), joints (beam-column joints and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(8 citation statements)
references
References 45 publications
0
8
0
Order By: Relevance
“…(7) I-shaped steel strength It can be seen from Figure 36 that with the increase in the strength of the profiled steel, its bottom plate lags behind its tensile steel bar in terms of yield time, and the beam's displacement ductility coefficient presents a nonlinear, decreasing trend. (8) With or without bonding As shown in Figure 37, when the prestressed steel strand had been bonded, the beam displacement ductility coefficient decreased, but this effect was not obvious. The rigidity of beams could thus be improved by the bonding method, such that their limit displacement can be reduced.…”
Section: Influence Of Resistance To Ductility (1) Reinforcement Ratio...mentioning
confidence: 99%
See 1 more Smart Citation
“…(7) I-shaped steel strength It can be seen from Figure 36 that with the increase in the strength of the profiled steel, its bottom plate lags behind its tensile steel bar in terms of yield time, and the beam's displacement ductility coefficient presents a nonlinear, decreasing trend. (8) With or without bonding As shown in Figure 37, when the prestressed steel strand had been bonded, the beam displacement ductility coefficient decreased, but this effect was not obvious. The rigidity of beams could thus be improved by the bonding method, such that their limit displacement can be reduced.…”
Section: Influence Of Resistance To Ductility (1) Reinforcement Ratio...mentioning
confidence: 99%
“…When UHPC is used in actual engineering, the amount of carbon dioxide and harmful gases emitted during the preparation process is greatly reduced compared with ordinary concrete, making it more green, environmentally friendly, and energy-saving [6]. UHPC has no coarse aggregates, and the particles are mostly densely packed and mixed with fibers, which are the basis of its good fracture toughness [7], allowing structures in which it is used to have greater free deformation and plastic deformation, thereby potentially improving the dynamic performance of the structure [8,9] and its anti-knock and impact resistance [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…Reinforced concrete (RC) shear wall (SW) is a common anti-lateral force component in high-rise buildings that has been widely used in high-frequent earthquake-prone areas [1][2][3][4][5]. The observation from recent earthquake reconnaissance indicated that the main reason why the RC SW was seriously damaged and even collapsed was its inadequate ductility and energy dissipation [6][7][8]. There are many problems that need to be solved urgently in the existing ordinary reinforced concrete SW located in high-intensity earthquake areas.…”
Section: Introductionmentioning
confidence: 99%
“…Research on fiber-reinforced concrete (FRC) underscores the advantageous characteristics fibers confer, depending on the fiber type and loading conditions. This encompasses topics such as the flexural behavior of FRC beams using single and hybrid steel fibers [6][7][8][9][10], shear behavior [11][12][13], performance under cryogenic temperatures [14,15], seismic response [16], effects of age [17], and more. The addition of fibers, especially steel ones, enhances not only tensile strength but also other crucial parameters in concrete behavior, such as compressive, shear, and flexural strength, corrosion resistance, and freeze-thaw resilience.…”
Section: Introductionmentioning
confidence: 99%